Low-Grade Ilmenite Leaching Kinetics Using Hydrochloric Acid: RSM and SCM Approaches - Supriyatna, Yayat Iman; Prasetya, Agus; Astuti, Widi; Sumardi, Slamet; Natalia, Priskila; Adythia, Dicky Marsa; Petrus, Himawan Tri Bayu Murti (Universitas Gadjah Mada, 2024)
Minerals containing TiO2 are common in Indonesia, such as ilmenite in iron sand deposits scattered along the country's coasts. Ilmenite is an important source of titanium. One method for making TiO2 from ilmenite is by solubilizing both the Fe and Ti elements in HCl and then immediately hydrolyze the Ti. The leaching of low-grade ilmenite (ground to 0.177-0.149 mm) is studied kinetically by HCl in a stirred reactor. The research was conducted using the caustic fusion method followed by HCl leaching. The leaching reaction kinetics at the optimum conditions are analyzed using response surface methodology (RSM) with a second-order polynomial equation model and SSE with the shrinking core model (SCM). The results showed that HCl concentration and leaching time were directly proportional to the leached titanium concentration. In contrast, the leaching temperature was inversely proportional. The optimum operating conditions were obtained at a temperature of 30 °C, 9 M HCl, and 120 min of leaching time. The shrinking core model is a better representation of the kinetics than RSM with a second-order polynomial equation model. Based on SCM, the rate of the leaching reaction of titanium from low-grade ilmenite is controlled by diffusion through the ash layer.